Chapter «Recevì la vostra litera a la quale e respondo». Qualche nota intorno alle reti epistolari del Trecento padano - Lazzarini, Isabella (Reti Medievali E-Book, 2021)
My essay focuses on the correspondences sent to the Gonzaga of Mantua and received and preserved in the Mantuan chancery during the 14th century. The broad range of correspondences gathered in the Mantuan archives covers almost all the north and central Italy, from Tuscany to the Val d'Adige, from Genoa to Venice. Its quantity and variety open the gate to a most needed investigation of the epistolary forms of political and diplomatic communication in the 14th century, therefore fostering a better understanding of this crucial period, squeezed between the better known communal Duecento and princely Quattrocento.